Profil Vertikal Oksigen Terlarut di Zona Lakustrin dan Transisi Waduk Plta Koto Panjang Kabupaten Kampar Provinsi Riau - Azmudin '; Asmika H Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted from July to September 2013 in PLTA Koto PanjangReservoir Kampar Regency, Riau Province. This research aims to see the vertical profile ofdissolved oxygen in lacustrine and transition zone in the PLTA Koto Panjang reservoir, seethe depth is safe for the concentration of dissolved oxygen for aquaticlife organisms and todetermine the effect of oxygen on the KJA to lacustrine and transition zone . Water sampleswere collected from four station, namely station L1 and L2 in lacustrine zone, T1 and T2 intransition zone. In each station, vertikal sampling is determined based on transparancy namelyin the surface, 2 Secchi depth (3 meters), 4 secchi depth (6 meters), 12 meters and in thebottom. Sample was done three time and sampling interval three week. The water qualityparameters measured were dissolved oxygen, free carbon dioxide, pH, nitrate, phosphate,temperature, depth, transparency, and phytoplankton abundance.The result shown dissolved oxygen in the surface range 7,14 – 7,94 mg/L, 2 secchidepth 5,35 – 7,81 mg/L, 4 secchi depth 3,01 – 4,67 mg/L, 12 meters 0,68 – 2,33 mg/L and inthe bottom 0,14 – 1,37 mg/L. CO2 range 5,32 – 38,62 mg/L, pH 5,50 – 5,83, nitrate 0,24 –0,32 mg/L, 0,02 – 0,14 mg/L, temperature 27,67 – 32,33 0C, depth 9,1 – 23,9 m, transparancy86 – 111,67 cm, phytoplankton abundance range 54.004 – 83.469 cells/L. Based on theverikal profil of dissolved oxygen shown the concentration of dissolved oxygen decreaseswith increasing depth. In the lacustrine zone of dissolved oxygen concentration has anoksix at12 m.Keyword : Dissolved Oxygen, Vertical Profile, PLTA Koto Panjang Reservoir